SO2 adsorption on carbon-supported Pt electrocatalysts - Punyawudho K. (2017)
Adsorption of SO 2 on a Pt/C catalyst typically used in proton exchange- membrane fuel cells (PEMFCs) has been investigated by temperature programmed desorption (TPD). SO 2 concentrations in N 2 were varied from 5 ppm to 1% (vol) and adsorption isotherms were determined at 25, 50, and 80 °C. Oxygen assisted (O-assisted) desorption experiments (i.e., successive TPD experiments following exposure to room temperature O 2 after the first TPD event) produced an additional SO 2 peak at a temperature higher than the initial SO 2 peak. These two types of SO 2 adsorption were identified as weakly adsorbed SO 2 species desorbed between 140 and 200 °C, depending on concentration, and a strongly adsorbed, dissociated species. For the strongly adsorbed, dissociative species, 18 O 2 isotope introduction during O-assisted desorption yielded ratios of 50%, 36%, and 14% for SO 2 masses of 64, 66, and 68, respectively. The activation energy and kinetic constant of desorption are reported for weakly adsorbed SO 2 at 1% and 20 ppm SO 2 using the Polanyi-Wigner equation. © 2011 American Chemical Society.